Clinical features of heart failure with mid‐range and preserved ejection fraction in octogenarians: Results of a multicentre, observational study. Issue 4 (21st March 2019) - Özlek, Bülent; Özlek, Eda; Tekinalp, Mehmet; Kahraman, Serkan; Ağuş, Hicaz Zencirkıran; Çelik, Oğuzhan; Çil, Cem; Kaya, Bedri Caner; Rencüzoğulları, İbrahim and Mert, Kadir Uğur and Çakır, Mustafa Ozan and Ösken, Altuğ and Bekar, Lütfü and Çelik, Yunus and Başaran, Özcan and Doğan, Volkan and Mert, Gurbet Özge and Sancar, Kadriye Memiç and Sevinç, Samet and Biteker, Murat
Summary: Objectives: To compare real‐world characteristics and management of individuals aged 80 and older with heart failure (HF) and mid‐range ejection fraction (HFmrEF) and heart failure with preserved ejection fraction (HFpEF) derived from a large cohort of survey and to compare them with those younger than 80 from the same survey. Methods: This is an observational, multicentre and cross‐sectional study conducted in Turkey (NCT03026114). Consecutive 1065 (mean age of 67.1 ± 10.6 years) patients admitted to the cardiology outpatient units with HFmrEF and HFpEF were included. Results: Participants aged 80 and older (n = 123, 11.5%) were more likely to be female (66.7% vs 52.5%, P = 0.003), had a higher prevalence of atrial fibrillation (49.6% vs 34%, P = 0.001), and anaemia (46.3% vs 33.4%, P = 0.005) than those who were younger than 80. N‐terminal pro B‐type natriuretic peptide levels were higher in those aged 80 and older than in those younger than 80 (1037 vs 550 pg/ml, P < 0.001). The prescription rates of HF medications (including in ACE‐Is/ARBs, β‐blockers, MRAs, digoxin, ivabradine and diuretics) were similar ( P > 0.05) in both groups. Octogenarians did not significantly differ from younger patients in the prevalence of HFmrEF (24.4% vs 22.9%) and HFpEF (75.6% vs 77.1%). Coronary artery disease was associated with HFmrEF ( P < 0.05), whereas atrial fibrillation was associated with HFpEF ( P < 0.05) in octogenarians. Conclusions: This study revealed that nearly 12% of the individuals with HFmrEF and HFpEF in this real‐world sample were aged 80 and older. Participants aged 80 and older are more likely to be female and have more comorbidities than those who were younger than 80. However, HF medication profiles were similar in both groups. This study also showed that associated factors with HFmrEF and HFpEF were differ in octogenarians.